Kuliah Kerja Nyata: Proyek Pembuatan Shade House untuk Pembibitan Kopi Liberika Lokpaikat di Desa Puncak Harapan, Tapin, Kalsel: Community Service Program: Shade House Construction Project for the Lokpaikat Liberica Coffee Nursery in Puncak Harapan Village, Tapin, South Kalimantan - Hidayat, Findi; Nengseh, Puji Astuti; Salsabila, Khairunnisa; Mustiarah, Fitri; Viola, Astor; Saputra, Riza Adrianoor (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Coffee is a plantation commodity that requires shade. Puncak Harapan Village is a rubber-growing area, with coffee plants growing among the rubber trees. However, obtaining superior, ready-to-plant coffee seedlings is difficult, so a coffee shade house was built to make it easier for the community to obtain Liberica coffee seedlings and to maximize the use of rubber plantation land. The purpose of this activity is to ensure that unplanted coffee seedlings can be properly cared for before being transplanted among the rubber plants. The implementation method includes a location survey for the shade house, land clearing, construction of the shade house, and planting Liberica coffee seedlings. This shade house is built with dimensions of 10 x 15 m2 and a height of 1.5 m on the left and right sides, while the center side is 3 m high. The top of the shade house is covered with a net to shade the coffee seedlings from direct sunlight. After the nursery process was completed, a symbolic inauguration was held by the Puncak Harapan Village Head and attended by representatives of the village government. This shade house will help develop coffee cultivation among the rubber plants in Puncak Harapan Village.